DETERMINATION OF INSULIN GENE INSG POLYMORPHISMS AND THEIR RELATIONSHIP WITH SOME PRODUCTIVE TRAITS IN BOTH SEXES OF HYBRID BROILER ROSS308 - & Mohamed, Al- Alanbari (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
To determine the polymorphisms of Insulin gene INSg and its relationship with some productive traits such as rate of initial and weekly body weight, average weekly body gain, live body weight, carcass weight, dressing %, cuts weight and weight for abdominal fat on broiler  in both sexes for Ross 308  hybrid, 200 one – day old chicks, reared on closed system tagged and weighted initially and weekly for 35 days, polymorphisms for Insulin gene were determined by using MSPI restriction enzyme and PCR-RFLP technique. Results showed two genotypes were detected only for INSg differ highly significantly P